Prognostic and therapeutic role of targetable lesions in B-lineage acute lymphoblastic leukemia without recurrent fusion genes - Messina, Monica; Chiaretti, Sabina; Wang, Jiguang; Fedullo, Anna Lucia; Peragine, Nadia; Gianfelici, Valentina; Piciocchi, Alfonso; Brugnoletti, Fulvia; Di Giacomo, Filomena; Pauselli, Simona; Holmes, Antony B.; Puzzolo, Maria Cristina; et al. (Oncotarget, 2016)
To shed light into the molecular bases of B-lineage acute lymphoblastic leukemia lacking known fusion transcripts, i.e. BCR-ABL1, ETV6-RUNX1, E2A-PBX1, and MLL rearrangements (B-NEG ALL) and the differences between children, adolescents/young adults (AYA) and adults, we analyzed 168 B-NEG ALLs by genome-wide technologies. This approach showed that B-NEG cases carry 10.5 mutations and 9.1 copy-number aberrations/sample. The most frequently mutated druggable pathways were those pertaining to RAS/RTK (26.8%) and JAK/STAT (12.5%) signaling. In particular, FLT3 and JAK/STAT mutations were detected mainly in AYA and adults, while KRAS and NRAS mutations were more frequent in children. RAS/RTK mutations negatively affected the outcome of AYA and adults, but not that of children. Furthermore, adult B-NEG ALL carrying JAK/STAT mutations had a shorter survival. In vitro experiments showed that FLT3 inhibitors reduced significantly the proliferation of FLT3-mutated primary B-NEG ALL cells. Likewise, PI3K/mTOR inhibitors reduced the proliferation of primary cells harboring RAS and IL7R mutations. These results refine the genetic landscape of B-NEG ALL and suggest that the different distribution of lesions and their prognostic impact might sustain the diverse outcome between children, adults and partly AYA - whose genomic scenario is similar to adults - and open the way to targeted therapeutic strategies.